Assumptions and development of the Digital Single Market in the context of economic growth in the European Union - Pleśniarska, Aleksandra (Założenia i rozwój jednolitego rynku cyfrowego w aspekcie wzrostu gospodarczego w Unii Europejskiej, 2019)
The digital revolution, the Internet and digitisation have fundamentally influenced human life, businesses, trade and the development of the economy. Globalisation has entered a new phase “underpinned by the movement of data across national borders, changing the nature, patterns and actors in international trade in goods and services” [OECD 2017, p. 2]. As a consequence of the ongoing phenomena, there are also changes within the framework of the functioning of the single market in the European Union (EU). The aim of the article is to present the main assumptions of the Digital Single Market (DSM) in the European Union and the state of their implementation. The adopted research method includes a literature survey, a study of the strategic documents of the European Union and their critical analysis. The article systematizes knowledge of the Digital Single Market in the European Union and completes it with the presentation of selected data, which allows for a better understanding of its significance for the development of European integration and economic growth
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 103-113
Keywords: digital single market; European Union; economic growth; digital economy; jednolity rynek cyfrowy; Unia Europejska; wzrost gospodarczy; gospodarka cyfrowa